Significant changes in advanced lung cancer survival during the past decade in Hungary: impact of modern immunotherapy and the COVID-19 pandemic - Kiss, Zoltán; Gálffy, Gabriella; Müller, Veronika; Moldvay, Judit; Sárosi, Veronika; Pápai-Székely, Zsolt; Csada, Edit; Kerpel-Fronius, Anna; Király, Zsolt; Szász, Zoltán; Hódi, Gábor; Polányi, Zoltán; et al. (Frontiers in Oncology, 2023)
Objective: The approval of immunotherapy (I-O) for the treatment of late-stage non-small cell lung cancer (NSCLC) opened new perspectives in improving survival outcomes. However, survival data have not yet been provided from the period of the Covid-19 pandemic. The aims of our study were to assess and compare survival outcomes of patients with advanced LC receiving systemic anticancer treatment (SACT) before and after the approval of immunotherapy in Hungary, and to examine the impact of pandemic on survival outcomes using data from the Hungarian National Health Insurance Fund (NHIF) database. Methods: This retrospective, longitudinal study included patients aged ≥20 years who were diagnosed with advanced stage lung cancer (ICD-10 C34) between 1 January 2011 and 31 December 2021 and received SACT treatment without LC-related surgery. Survival rates were evaluated by year of diagnosis, sex, age, and LC histology. Results: In total, 35,416 patients were newly diagnosed with advanced LC and received SACT during the study period (mean age at diagnosis: 62.1–66.3 years). In patients with non-squamous cell carcinoma, 3-year survival was significantly higher among those diagnosed in 2019 vs. 2011–2012 (28.7% [95% CI: 26.4%–30.9%] vs. 14.45% [95% CI: 13.21%–15.69%], respectively). In patients with squamous cell carcinoma, 3-year survival rates were 22.3% (95% CI: 19.4%–25.2%) and 13.37% (95% CI: 11.8%–15.0%) in 2019 and 2011–2012, respectively, the change was statistically significant. Compared to 2011–2012, the hazard ratio of survival change for non-squamous cell carcinoma patients was 0.91, 0.82, and 0.62 in 2015–2016, 2017–2018, and 2019, respectively (p<0.001 for all cases). In the squamous cell carcinoma group, corresponding hazard ratios were 0.93, 0.87, and 0.78, respectively (p<0.001 for all cases). Survival improvements remained significant in both patient populations during the Covid-19 pandemic (2020–2021). No significant improvements were found in the survival of patients with small cell carcinoma. Conclusion: 3-year survival rates of NSCLC almost doubled among patients with non-squamous cell carcinoma and significantly improved at squamous cell carcinoma over the past decade in Hungary. Improvements could potentially be attributable by the introduction of immunotherapy and were not offset by the Covid-19 pandemic.